Identification of phagocytosis regulators using magnetic genome-wide CRISPR screens. (December 2018) - Haney, Michael; Bohlen, Christopher; Morgens, David; Ousey, James; Barkal, Amira; Tsui, C.; Ego, Braeden; Levin, Roni; Kamber, Roarke; Collins, Hannah; Tucker, Andrew; Li, Amy; et al.
Abstract Phagocytosis is required for a broad range of physiological functions, from pathogen defense to tissue homeostasis, but the mechanisms required for phagocytosis of diverse substrates remain incompletely understood. Here, we developed a rapid magnet-based phenotypic screening strategy, and performed eight genome-wide CRISPR screens in human cells to identify genes regulating phagocytosis of distinct substrates. After validating select hits in focused miniscreens, orthogonal assays and primary human macrophages, we show that (1) the previously uncharacterized geneNHLRC2 is a central player in phagocytosis, regulating RhoA-Rac1 signaling cascades that control actin polymerization and filopodia formation, (2) very-long-chain fatty acids are essential for efficient phagocytosis of certain substrates and (3) the previously uncharacterized Alzheimer's disease–associated geneTM2D3 can preferentially influence uptake of amyloid-β aggregates. These findings illuminate new regulators and core principles of phagocytosis, and more generally establish an efficient method for unbiased identification of cellular uptake mechanisms across diverse physiological and pathological contexts. Eight genome-wide CRISPR screens identify genes required for substrate-specific phagocytosis. The study highlights roles forNHLRC2 in filopodia formation, very-long-chain fatty acids in substrate-specific phagocytosis andTM2D3 in uptake of amyloid-β aggregates.